2008
DOI: 10.1038/bjp.2008.266
|View full text |Cite
|
Sign up to set email alerts
|

Palosuran inhibits binding to primate UT receptors in cell membranes but demonstrates differential activity in intact cells and vascular tissues

Abstract: Background and purpose: The recent development of the UT ligand palosuran (1-[2-(4-benzyl-4-hydroxy-piperidin-1-yl)-ethyl]-3-(2-methyl-quinolin-4-yl)-urea sulphate salt) has led to the proposition that urotensin-II (U-II) plays a significant pathological role in acute and chronic renal injury in the rat. Experimental approach: In the present study, the pharmacological properties of palosuran were investigated further using a series of radioligand binding and functional bioassays. Key results: Palosuran functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 45 publications
(101 reference statements)
1
38
1
Order By: Relevance
“…In a subsequent study in type 2 diabetics, palosuran demonstrated no clinically significant effects on ␤-cell secretory capacity and no effects on first-and secondphase insulin response (109). The reason for these disappointing results has been largely ascribed to a poor dosing regimen, as 125 mg of palosuran twice daily translates to a peak plasma concentration of Ͻ 260 nM, Ͼ 10-fold lower than the reported UT affinity for palosuran in mammals (8).…”
Section: Potential Therapeutic Applicationsmentioning
confidence: 97%
See 1 more Smart Citation
“…In a subsequent study in type 2 diabetics, palosuran demonstrated no clinically significant effects on ␤-cell secretory capacity and no effects on first-and secondphase insulin response (109). The reason for these disappointing results has been largely ascribed to a poor dosing regimen, as 125 mg of palosuran twice daily translates to a peak plasma concentration of Ͻ 260 nM, Ͼ 10-fold lower than the reported UT affinity for palosuran in mammals (8).…”
Section: Potential Therapeutic Applicationsmentioning
confidence: 97%
“…Thus, palosuran may help to alleviate portal hypertension (131). Despite the results, it was proposed that in the rat study on renal ischemia-reperfusion, only approximately half the dose necessary for efficacy was given (8), as a dose of 10 mg/(kg·h) translates to a plasma concentration of only 5 M (123). In addition, it should be noted that the binding affinity of palosuran in rats is very low (123).…”
Section: Potential Therapeutic Applicationsmentioning
confidence: 99%
“…These IC 50 values were very close to those from the radiolignad-binding assay (2.0 nM). 19 Excellent correlation coefficients were obtained in both assay methods (0.98 and 0.97 for FP-and TRF-based UT receptor binding assays, respectively) and the Hill slopes were evaluated as -1.3 for FP-based UT receptor binding assay and -1.7 for TRF-based binding assay. These results imply that current FP-and TRF-based UT receptor binding assays can mimic the classical detection results as in the radioligand receptor binding assay without numerous limitations of isotopic experiments.…”
Section: Inhibition Of Ligand Binding Activities By Uiimentioning
confidence: 78%
“…For FP-based receptor binding assay, an FITC-labeled human recombinant UII (FITCGlu-Thr-Pro-Asp-Cys-Phe-Trp-Lys-Tyr-Cys-Val) was obtained from Phoenix Pharmaceuticals, Inc. (Burlingame, CA). As UT receptor selective reference compounds, 1-[2-(4-benzyl-4-hydroxy-piperidin-1-yl)-ethyl]-3-(2-methyl-quinolin-4-yl)-urea sulfate salt (palosuran) 18 and 2-bromo-N-[4-chloro-3-((R)-1-methyl-pyrrolidin-3-yloxy)-phenyl]-4,5-dimethoxybenzenesulphonamide HCl (SB657510) 19 were synthesized in-house. Pluronic F-127 was purchased from Invitrogen (Carlsbad, CA) and 1 M MgCl 2 was obtained from Amresco, Inc. (Solon, OH).…”
Section: Reagentsmentioning
confidence: 99%
“…However, the existence of marked differences between the prior investigation and the current study regarding the antagonist used (SB-710411 vs. palosuran), the experimental model (ccl 4 vs. bile duct ligation rats) and the experimental design (preventive effect for 8 weeks vs. therapeutic effect for 3 days) makes it difficult to identify the reason for this discrepancy. Moreover, responses to palosuran cannot be replicated with alternate uT antagonists, such as SB-710411 (41). Although drug efficacy cannot be directly compared because of variations in study parameters, it is evident that SB-710411 attenuated fibrosis in a fashion similar to other therapeutic modalities, including angiotensin-converting enzyme inhibitors.…”
Section: Discussionmentioning
confidence: 99%